Cerebral microbleeds in vascular dementia from clinical aspects to host-microbial interaction. (September 2021) - Tonomura, Shuichi; Gyanwali, Bibek
Abstract: Vascular dementia is the second leading cause of dementia after Alzheimer's disease in the elderly population worldwide. Cerebral microbleeds (CMBs) are frequently observed in MRI of elderly subjects and considered as a possible surrogate marker. The number and location of CMBs reflect the severity of diseases and the underlying pathologies may involve cerebral amyloid angiopathy or hypertensive vasculopathy. Accumulating evidence demonstrated the clinicopathological discrepancies of CMBs, the clinical significance of CMBs associated with other MRI markers of cerebral small vessel disease, cognitive impairments, serum, and cerebrospinal fluid biomarkers. Moreover, emerging evidence has shown that genetic factors and gene-environmental interactions might shed light on the underlying etiologies of CMBs, focusing on blood-brain-barrier and inflammation. In this review, we introduce recent genetic and microbiome studies as a cutting-edge approach to figure out the etiology of CMBs through the "microbe-brain-oral axis" and "microbiome-brain-gut axis." Finally, we propose novel concepts, "microvascular matrisome" and "imbalanced proteostasis, " which may provide better perspectives for elucidating the pathophysiology of CMBs and future development of therapeutics for vascular dementia using CMBs as a surrogate marker. Highlights: Cerebral microbleeds is a surrogate marker of cerebral small vessel diseases. We propose possible gene-gene and gene-environmental interactions. "matrisome" and "proteostasis" are key etiologies of cerebral microbleeds.